Locoregional effects of microbiota in a preclinical model of colon carcinogenesis - Tomkovich, Sarah (Cancer Res, 2017)
Inflammation and microbiota are critical components of intestinal tumorigenesis. To dissect how the microbiota contributes to tumor distribution, we generated germ-free (GF) Apc(Min/+) and Apc(Min/+);Il10(−/−) mice and exposed them to specific-pathogen-free (SPF) or colorectal cancer-associated bacteria. We found colon tumorigenesis significantly correlated with inflammation in SPF housed Apc(Min/+);Il10(−/−), but not Apc(Min/+) mice. In contrast, small intestinal neoplasia development significantly correlated with age in both Apc(Min/+);Il10(−/−) and Apc(Min/+) mice. GF Apc(Min/+);Il10(−/−) mice conventionalized by an SPF microbiota had significantly more colon tumors compared to GF mice. Gnotobiotic studies revealed that while Fusobacterium nucleatum clinical isolates with FadA and Fap2 adhesins failed to induce inflammation and tumorigenesis, pks+ Escherichia coli promoted tumorigenesis in the Apc(Min/+);Il10(−/−) model in a colibactin-dependent manner, suggesting colibactin is a driver of carcinogenesis. Our results suggest a distinct etiology of cancers in different locations of the gut, where colon cancer is primarily driven by inflammation and the microbiome, while age is a driving force for small intestine cancer.